Shared Governance: A Way to Improve the Care in an Inpatient Rehabilitation Facility. Issue 2 (11th April 2014) - Torres, Audrey; Kunishige, Nalani; Morimoto, Denise; Hanzawa, Tracie; Ebesu, Mike; Fernandez, John; Nohara, Lynne; SanAgustin, Eliseo; Borg, Stephanie
Abstract Background Rehabilitation care is specialized and individualized requiring effective and efficient communication to achieve optimal patient outcomes. Purpose To examine how effective implementation of shared governance could improve care delivery, promote patient‐centered care, and improve patient outcomes. Design The shared governance approach included all members of the rehabilitation team (i.e., physical therapist, occupational therapist, speech therapist, registered nurse and nurse aide) and was implemented over 6 months. Findings/Conclusions The major end products of this shared governance effort were improved staff communication, problem solving, patient outcomes, and staff satisfaction on our stroke and brain injury unit. Clinical Relevance When effectively implemented and sustained, shared governance between all rehabilitation team stakeholders can increase the effectiveness of communication along with more positive patient and staff outcomes.